Advances in manufacturing and mechanical engineering : selected, peer reviewed papers from the International Conference on Advances in Mechanical Engineering 2013 (ICAME 2013), 28-29, August 2013, Malacca, Malaysia - Kuntjoro, Wahyu (Applied mechanics and materials ;, 2013)
Collection of selected, peer reviewed papers from the International Conference on Advances in Mechanical Engineering 2013 (ICAME 2013), August 28-29, 2013, Malacca, Malaysia. The 161 papers are grouped as follows: Chapter 1: Advanced Manufacturing and Industrial Processes; Chapter 2: Advanced Materials, Materials Processing and Forming; Chapter 3: Advances in Aerospace and Automotive; Chapter 4: Mechanics of Solids and Structures, Impact Mechanics; Chapter 5: Powertrains and Alternative Fuels; Chapter 6: Robotics and Mechatronics, Detection and Recognition; Chapter 7: System Dynamics, Vibratio.